Investigation of the cumulative number of chromosome aberrations induced by three consecutive CT examinations in eight patients. (28th October 2019) - Abe, Yu; Noji, Hideyoshi; Miura, Tomisato; Sugai, Misaki; Kurosu, Yumiko; Ujiie, Risa; Tsuyama, Naohiro; Yanagi, Aki; Yanai, Yukari; Ohba, Takashi; Ishikawa, Tetsuo; Kamiya, Kenji; et al.
Abstract: In our previous study, we found that chromosomes were damaged by the radiation exposure from a single computed tomography (CT) examination, based on an increased number of dicentric chromosomes (Dics) formed in peripheral blood lymphocytes after a CT examination. We then investigated whether a cumulative increase in the frequency of Dics and chromosome translocations (Trs) formation could be observed during three consecutive CT examinations performed over the course of 3–4 years, using lymphocytes in peripheral bloods of eight patients (five males and three females; age range 27–77 years; mean age, 64 years). The effective radiation dose per CT examination estimated from the computational dosimetry system was 22.0–73.5 mSv, and the average dose per case was 40.5 mSv. The frequency of Dics formation significantly increased after a CT examination and tended to decrease before the next examination. Unlike Dics analysis, we found no significant increase in the frequency of Trs formation before and after the CT examination, and we observed no tendency for the frequency to decrease before the next CT examination. The frequency of Trs formation was higher than that of Dics formation regardless of CT examination. Furthermore, neither analysis of Dics nor Trs showed a cumulative increase in the frequency of formation following three consecutive CT examinations.